A Stage for the Unknown? Reconciling Postwar Communities through Theatre-Facilitated Dialogue. (12th March 2020) - Dirnstorfer, Anne; Saud, Nar Bahadur
Abstract: The article explores the potential of theatre art in transitional justice, particularly in the field of reconciliation and healing. Presenting the context of reconciliation in Nepal 10 years after the end of the armed conflict, the authors argue for complementary processes of top-down and community-based, bottom-up approaches by introducing the concept of 'theatre-facilitated dialogue' as a way to strategically integrate Playback Theatre in peacebuilding. Analyzing the project 'EnActing Dialogue, ' the article elaborates on the learnings from theatre-facilitated dialogue work in communities where ex-combatants of the Nepali People's Liberation Army have settled. Based on the theoretical overview of secondary resources, the authors' participatory observations, on informal interviews and quantitative data, the study explores how artistically enacted storytelling supports bottom-up reconciliation. By staging a noncognitive dialogue through storytelling, music and theatre, Playback Theatre contributes to the deconstruction of war-related identities, an understanding of root causes, as well as personal healing and relationship building at community level.